The holy war : the losing and taking again of the town of Mansoul - Bunyan, John, 1628-1688.; Smith, Wilbur M. (Wilbur Moorehead), 1894-1976. (Chicago : Baker books, 1979)
Lloyd M. Perry Collection.
Includes indexes.
Bibliography: p. 365-368.
Keywords: Spiritual warfare -- Fiction